Geriatrics Syndrome Research in Focus: A Bibliometric Overview - Nova Relida Samosir; Azliyana Azizan (Jurnal teknologi Kesehatan Borneo, 2024)
The bibliometric study provides an extensive summary of academic publications from 1990 to 2024 that are indexed in Web of Science (WoS) and Scopus. It highlights important research issues within geriatric syndromes, institutional contributions, regional distribution, and publication trends. 331 publications are listed in WoS, compared to 126 in Scopus. The yearly distribution patterns of the two databases are comparable, with noteworthy peaks occurring in 2000, 2010, and 2019. Strangely, there are no articles in 2024 according to both databases, which calls for more research. After Japan (35), Spain (28), and the United States (42) in terms of publications per country. Well-known establishments are Harvard Medical School and Johns Hopkins University. Two of the most often referenced studies, Inouye et al. (2007) and Tinetti et al. (1995), focus on important geriatric disorders, sarcopenia and frailty. With 25 publications, the Journal of the American Geriatrics Society takes first place. Six theme clusters, comprising fundamental concerns like disability, falls, and frailty, are revealed using keyword co-occurrence analysis. The results emphasize the necessity of ongoing financing for research on aging syndromes and draw attention to important research gaps and new trends. The sharp decline in 2024 publication numbers and dependence on two databases are acknowledged drawbacks that point to areas in need of greater research and thorough examinations in the future.